(untitled) (KONFERENSIYA, 2025)
This article provides an in-depth exploration of how translation studies have developed in Uzbekistan, outlining the modern difficulties and future opportunities in the field. It highlights the valuable role of the nation’s historical translation legacy, which acts as a bridge between the past and the future and supports the growth of scientific and educational approaches to translation. Translation is described as an essential tool for revealing cultural identity — a process visible throughout history, as renowned Uzbek scholars have greatly shaped the formation of translation studies as a separate academic area